Catalytic ignition of hydrogen and hydrogen-hydrocarbon blends over noble metals - Rubtsov, Nickolai M.; Troshin, Kirill Ya; Alymov, Michail I. (Heat and mass transfer,, 2023)
This book examines the issues on noble metal influence on gaseous combustion. The book focuses on the new data on combustion processes having practical applications and includes fire safety issues in the use of noble metals in hydrogen recombiners for NPP, as well as in catalytically stabilized (CS) combustion technology including stimulation of combustion of hydrogen-blended hydrocarbons, synthesis of carbon nanotubes, and determination of catalytic ignition limits in noble metal-hydrogen-hydrocarbon systems to meet the challenges of explosion safety.